Latest Generation of Balloon-Expandable Valve, the Edwards Sapien 3 Valve: Less Paravalvular Regurgitation but Higher Transvalvular Pressure Gradients - Eghbalzadeh, Kaveh; Kuhn, Elmar W.; Sabashnikov, Anton; Weber, Carolyn; Rahmanian, Parwis Baradaran; Siedek, Florian; Mauri, Victor; Rudolph, Tanja; Baldus, Stephan; Madershahian, Navid; Wahlers, Thorsten C. (The Thoracic and Cardiovascular Surgeon, 2019)
Background The latest generation of balloon-expandable valve, the Edwards Sapien 3 valve (S3V), was designed to reduce paravalvular regurgitation (PVR). We retrospectively compared S3V with Edwards Sapien XT valve (SXTV) with regard to postprocedural transvalvular pressure gradients (PGs).Methods Analysis of 152 patients receiving SXTV and 125 patients receiving S3V between February 2009 and April 2015 was performed. Transvalvular PGs and the incidence and extent of aortic regurgitation (AR) were compared postprocedurally by echocardiography for each valve size.Results Postprocedurally, mean PGs for the 23 mm valves were 10.9 ± 5.3 versus 13.9 ± 5.1 (p = 0.017), whereas maximum PGs were 19.9 ± 8.3 versus 26.1 ± 10.4 mm Hg (p = 0.005) in SXTV and S3V patients, respectively. For the 26 mm valves, gradients were also significantly higher in S3V patients (mean PG: 11.6 ± 4.9 vs. 9.2 ± 4.2 [p = 0.004]; maximum PG: 23.0 ± 10.1 vs. 17.2 ± 7.4 mm Hg [p < 0.001]). Analysis revealed no significant differences in postprocedural transvalvular PGs for 29 mm valves (mean PG of 9.3 ± 3.9 and 11.2 ± 4.3 mm Hg [p = ns] and maximum PG of 17.5 ± 7.2 vs. 20.9 ± 6.8 mm Hg [p = ns]) between SXTV and S3V groups, respectively. With respect to PVR, the incidence of AR was significantly lower in S3V group (p = 0.001).Conclusion S3V shows lower incidence of PVR; however, it is associated with significantly higher postprocedural transvalvular PGs for 23 and 26 mm valve sizes. These data might contribute to the scientific discussion, especially with respect to prosthesis selection in individual patients with small annular dimension.
Keywords: aorta/aortic; echocardiography; heart; valve; transapical; percutaneous